Combination Between Root Pruning and Inoculation Time of Ectomycorrhizal Fungi on Improving Growth of Melinjo (Gnetum gnemon L) Seedling PENGARUH KOMBINASI PEMANGKASAN AKAR DAN WAKTU INOKULASI FUNGI EKTOMIKORIZA TERHADAP PERTUMBUHAN BIBIT MELINJO - Arum Sekar Wulandari; Siti Jaenab (Jurnal Silvikultur Tropika, 2016)
The inoculation of ectomycorrhizal fungi that conducted after root pruning could increase the colonization of ectomycorrhizal fungi and growth of melinjo seedling. This research aimed to study the effect of root pruning and inoculation time of ectomycorrhizal fungi on the growth of melinjo seedlings (Gnetum gnemon L). The research were tested in a greenhouse in a completely randomized design with 2 factors for 33 weeks. The first factor is the root pruning (no root pruning as a control, and root pruning 30%). The second factor is the time fungi inoculation (inoculation in the 1st, 2nd, 3rd, 4th and 5th week after root pruning). The combination of root pruning and inoculation time of ectomycorrhizal fungi effected to the growth of melinjo seedlings. The best growth obtained from combination (1) no root pruning and inoculated by ectomycorrhizal fungi in the 1st week, and (2) root pruning 30% and inoculated by ectomycorrhizal fungi in the 3rd week.Key words: ectomycorrhiza, Gnetum gnemon, inoculation time, root pruning, Scleroderma